Polarized training is optimal for endurance athletes: Response to Burnley, Bearden, and Jones - Foster, C.; Casado, A.; Esteve-Lanao, J.; Haugen, T.; Seiler, S. (Medicine & Science in Sports & Exercise, 2022)
Concluding statement. Athletes clearly benefit from performing both a high volume of low-intensity training and more measured volumes of high-intensity training. It may be that the TID has a unique specific effect on the benefit for training programs for endurance athletes. The concept of po larized training (z1 > z2 < z3) has become popular, although its near cousin, pyramidal training (z1 > z2 > z3), may be as effective. The relative merits of these two variations of training plans that are dominated by a large volume of relatively low intensity (hence nonspecific) training may depend on the spe cific event for which the training plan is designed. It may also reasonably be hypothesized that the large volume of low intensity training common to these variations in TID may re flect the need to have low monotony in the training plan. How ever, rather than the term "recovery days," perhaps a better term would be "training preparation days" because it may be necessary to have some recovery to allow for the large magni tude of homeostatic disturbances on "hard" training days, to mitigate orthopedic stress and to prevent autonomic dysfunc tion. The best recent evidence in athletes training for 5-km run ning races suggests the benefit of a polarized over a pyramidal TID, although these findings may reflect event specificity.